2012
DOI: 10.17221/14/2011-pps
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of various plant extracts against the early blight disease of tomato plants under greenhouse and field conditions

Abstract: The antimicrobial activity of six plant extracts from ocimum basilicum (Sweat Basil), Azadirachta indica (Neem), Eucalyptus chamadulonsis (Eucalyptus), Datura stramonium (Jimsonweed), Nerium oleander (Oleander), and Allium sativum (Garlic) was tested for controlling Alternaria solani in vitro and in vivo. In in vitro study the leaf extracts of D. stramonium, A. indica, and A. sativum at 5% concentration caused the highest reduction of mycelial growth of A. solani (44.4, 43.3 and 42.2%, respectively), while o. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
61
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(72 citation statements)
references
References 10 publications
10
61
0
1
Order By: Relevance
“…The results revealed that botanical extracts are capable of reducing anthracnose of chilli, quite significant even when applied singly. This result is in corroboration with some previous research works (Lakshmanan et al, 1990;Miah et al, 1990;Achimu and Schloesser, 1992;Nashwa and Abo-Elyousr, 2012;Ademe et al, 2013;Kabir et al, 2014). However, combinations of botanical extracts were more strong and effective even to a level that with minimum risk, such treatment can replace a highly effective chemical fungicidal treatment.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The results revealed that botanical extracts are capable of reducing anthracnose of chilli, quite significant even when applied singly. This result is in corroboration with some previous research works (Lakshmanan et al, 1990;Miah et al, 1990;Achimu and Schloesser, 1992;Nashwa and Abo-Elyousr, 2012;Ademe et al, 2013;Kabir et al, 2014). However, combinations of botanical extracts were more strong and effective even to a level that with minimum risk, such treatment can replace a highly effective chemical fungicidal treatment.…”
Section: Discussionsupporting
confidence: 93%
“…The combined treatments neem-garlic-mahagony and neem-mahagony-koromcha showed highly significant effect on the yield of broccoli reported by Kabir et al (2014). The fruit yield of different crops was increased by the use of different plant extracts are in agreement with the results of earlier investigations (Ngullie et al, 2010;Nashwa and Abo-Elyousr, 2012;Ademe et al, 2013).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…A number of plants have been reported to cause inhibition of several phytopathogenic fungi. [23,[36][37][38][39][40][41] [34] The petroleum ether extract exhibited significant antifungal activity against the test fungi. The leaf extract of S. crispus did not show any visible inhibition against Aspergillus brasiliensis and Candida albicans.…”
Section: Antibacterial Activity Of Extracts Of P Sessilismentioning
confidence: 99%
“…The pathogen can also attack potato tubers and symptoms are circular to irregular lesions that are slightly sunken and often surrounded by a raised purple to dark brown border and produce a shallow, dry, corky rot. [4,5] Estimating total annual crop losses due to any particular disease is difficult to do accurately.…”
mentioning
confidence: 99%